Liquid formulations pH: construction of novel robotic platform & data-driven pH adjustment - Sarfaraz Ahamed (Nanyang Technological University, 2023)
This report focuses on the construction of a new robotic platform designed to titrate complex, viscous liquid formulations of consumer products to a target pH. For complex, viscous mixtures the titration process is carried out manually in a slow trial and-error process by researchers. In this report, we accelerate the pH adjustment process by incorporating an overhead stirrer and pH probe in a single position, enabling the titration of viscous samples. The platform also features a washing station for full automation, allowing the robot to move between the closed-loop pH adjustment of different samples. The pH adjustment strategy uses a data-driven approach (Gaussian Process regression) combined with physical chemistry to develop a hybrid model capable of efficiently guiding the robotic platform to the target pH. In past research, there have been a development of a ML strategy compatible with strong-strong acid/base titrant pairs, while this report considers a weak-strong acid/base pair. The potential of forming a complex buffer solution if the target pH is overshot is addressed. The results of this study suggest that the new robotic platform and data-driven pH adjustment strategy have great potential for use in industrial high-throughput formulations workflows.